Capricornella bicornuta, a new genus and species of mite from eastern Australia (Acari: Uropodina) - Błoszyk, Jerzy; Halliday, Bruce; Adamski, Zbigniew; Książkiewicz-Parulska, Zofia (Zootaxa, 2017)
We describe a new genus and species of mite from eastern Australia, Capricornella bicornuta. The new genus is characterised by the presence of two long appendages on the anterior margin of the epigynal shield of the female.